Lithostratigraphy of the Naga-Manipur Hills (Indo-Burma Range) Ophiolite Belt from Ukhrul District, Manipur, India - Joshi, A; Vidyadharan, KT (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1272 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.73-74